De/constructing Literacies: Considerations for Engagement - Lemieux, Amélie (Peter Lang, 2020)
De/constructing Literacies: Considerations for Engagement reviews and defines the concept of engagement in literacy studies from different epistemologies. Well-suited for literacy researchers and graduate students, it considers the foundations of arts-based research, cognitive psychology, ethnography, phenomenology, posthumanism, with a final chapter on walking methodologies, to better understand how engagement can be framed and looked at in literacy studies.

Visualizing mapping as pedagogy for literacy futures - Lemieux, Amélie; Smith, A.; McLean, C.; Rowsell, Jennifer (Journal of Curriculum Theorizing, 2020)